2008
DOI: 10.1128/ec.00088-08
|View full text |Cite
|
Sign up to set email alerts
|

TOR1 and TOR2 Have Distinct Locations in Live Cells

Abstract: TOR is a structurally and functionally conserved Ser/Thr kinase found in two multiprotein complexes that regulate many cellular processes to control cell growth. Although extensively studied, the localization of TOR is still ambiguous, possibly because endogenous TOR in live cells has not been examined. Here, we examined the localization of green fluorescent protein (GFP) tagged, endogenous TOR1 and TOR2 in live S. cerevisiae cells. A DNA cassette encoding three copies of green fluorescent protein (3XGFP) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 44 publications
10
135
1
Order By: Relevance
“…In general, the TOR complexes were found to associate with membranes ranging from the plasma membrane to the vacuolar membrane and internal membranes of the protein secretory pathway (Cardenas and Heitman 1995;Kunz et al 2000;Wedaman et al 2003;Aronova et al 2007;Sturgill et al 2008;Berchtold and Walther 2009). TORC2 appears to be predominantly localized in discrete dots at the plasma membrane (Cardenas and Heitman 1995;Kunz et al 2000;Sturgill et al 2008), while TORC1 is mainly found at the vacuolar membrane, which is intriguing knowing that the vacuole is a reservoir of nutrients and that TORC1 signalling is believed to be regulated by nutrients (Cardenas and Heitman 1995;Aronova et al 2007;Sturgill et al 2008). According to a recent study, TORC1 is also targeted to the nucleus where it induces 35S rRNA synthesis under favourable growth conditions (Li et al 2006).…”
Section: The Tor Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the TOR complexes were found to associate with membranes ranging from the plasma membrane to the vacuolar membrane and internal membranes of the protein secretory pathway (Cardenas and Heitman 1995;Kunz et al 2000;Wedaman et al 2003;Aronova et al 2007;Sturgill et al 2008;Berchtold and Walther 2009). TORC2 appears to be predominantly localized in discrete dots at the plasma membrane (Cardenas and Heitman 1995;Kunz et al 2000;Sturgill et al 2008), while TORC1 is mainly found at the vacuolar membrane, which is intriguing knowing that the vacuole is a reservoir of nutrients and that TORC1 signalling is believed to be regulated by nutrients (Cardenas and Heitman 1995;Aronova et al 2007;Sturgill et al 2008). According to a recent study, TORC1 is also targeted to the nucleus where it induces 35S rRNA synthesis under favourable growth conditions (Li et al 2006).…”
Section: The Tor Pathwaymentioning
confidence: 99%
“…Conversely, TORC1 inactivation triggers (likely due to the activation of protein phosphatases) dephosphorylation of Rim15 at Thr 1075 , thereby favouring accumulation of Rim15 in the nucleus. Since Pho85-Pho80 is mainly localized within the nucleus and TORC1 is predominantly associated with the vacuolar membrane (Kaffman et al 1998a;Sturgill et al 2008), Pho85-Pho80 and TORC1 may act on different pools of Rim15. Interestingly, the intrinsic protein kinase activity of Rim15 is also required for its nuclear export .…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%
“…In contrast, lst8D only mildly reduced the expression of RPL3 and RPS6A, suggesting that lst8D does not lead to severe loss of TORC1 activity. Recent research has demonstrated that the TORC1 components are located on intracellular membranes with a concentration on the vacuolar membrane while TORC2 components appear as punctate spots at the plasma membrane (Wedaman et al 2003;Araki et al 2005;Sturgill et al 2008;Berchtold and Walther 2009;Binda et al 2009). It has been proposed that plasma membrane localization of TORC2 is essential for cell viability (Berchtold and Walther 2009).…”
Section: Sac7d and Far11d Mutants Are Sensitive To Rapamycinmentioning
confidence: 99%
“…EGOC, TORC1, and the downstream effector Sch9 are responsible for sensing and responding to amino acids, and all reside on the vacuolar membrane, congruent with the major role of the vacuole in amino acid storage (Cardenas and Heitman 1995;Huh et al 2003;Wedaman et al 2003;Jorgensen et al 2004;Araki et al 2005;Dubouloz et al 2005;Gao and Kaiser 2006;Sturgill et al 2008;Berchtold and Walther 2009;). While mammalian (m)TORC1 is recruited to the lysosome (vacuole equivalent) and activated in response to amino acids (Sancak et al 2008(Sancak et al , 2010, yeast TORC1 is constitutively located on the vacuole ) except under conditions of heat shock, whereupon TORC1 is sequestered into stress granules (Takahara and Maeda 2012).…”
mentioning
confidence: 95%